2017
DOI: 10.1016/j.drugalcdep.2016.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Reduced nicotine content cigarette advertising: How false beliefs and subjective ratings affect smoking behavior

Abstract: Introduction Tobacco advertising can create false beliefs about health harms that are reinforced by product design features. Reduced nicotine content (RNC) cigarettes may reduce harm, but research has not addressed advertising influences. This study examined RNC cigarette advertising effects on false harm beliefs, and how these beliefs – along with initial subjective ratings of RNC cigarettes – affect subsequent smoking behaviors. We further explored whether subjective ratings moderate associations between fal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…Two studies have examined associations between reduced nicotine cigarette risk perceptions and smoking behaviors. 9,11 Product perceptions were not directly associated with smoking behaviors in either study, although Mercincavage and colleagues found that greater false beliefs about reduced nicotine cigarettes were correlated with higher daily cigarette consumption among smokers who provided more favorable subjective ratings of the cigarettes. 11 Thus, there is limited data available to address how perceived health risks may influence initiation or long-term use of VLNC cigarettes or cessation.…”
Section: Perceptions and Behavior With Reduced Nicotine Content Cigarmentioning
confidence: 62%
“…Two studies have examined associations between reduced nicotine cigarette risk perceptions and smoking behaviors. 9,11 Product perceptions were not directly associated with smoking behaviors in either study, although Mercincavage and colleagues found that greater false beliefs about reduced nicotine cigarettes were correlated with higher daily cigarette consumption among smokers who provided more favorable subjective ratings of the cigarettes. 11 Thus, there is limited data available to address how perceived health risks may influence initiation or long-term use of VLNC cigarettes or cessation.…”
Section: Perceptions and Behavior With Reduced Nicotine Content Cigarmentioning
confidence: 62%
“…If nicotine in cigarettes were to become regulated, it would be imperative to educate the consumer that this product standard is not associated with a significant reduction in cigarette harm. Smokers tend to report misperceptions of the harms of cigarettes that are significantly reduced in levels of nicotine . These misperceptions are due largely to the erroneous belief that nicotine causes cancer or heart disease and, therefore, if nicotine is reduced in a product, then it would be safer.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our data extend this literature by examining multiple risk perceptions among an RNC-naïve sample. We hypothesized that, consistent with studies of previously commercially-available 15 and investigational 6,16 RNC cigarettes, smokers would misperceive RNC cigarettes as less harmful. Consistent with industry research, 19 we also hypothesized that age and gender would predict RNC cigarette risk perceptions, such that older and female smokers would be more likely to hold these misperceptions.…”
Section: Introductionmentioning
confidence: 85%
“…Indeed, the investigational RNC cigarette manufacturer used by recent trials has applied to the FDA to market its cigarettes as modified risk tobacco products. 14 Misperceptions about RNC cigarette risks may discourage cessation or promote increased product use, 15 negating potential benefits of mandated nicotine reduction.…”
Section: Introductionmentioning
confidence: 99%